An Overview of Stratospheric Ozone and Climate Effects - Karadan, M.M.; Raju, P.V.S.; Devara, P.C.S. (Earth and Planetary Science, 2022)
Anthropogenic Chlorofluorocarbons (CFCs) compelled stratospheric ozone reduction is one of the significant global environmental issues of this era. Ozone acts as a life saviour in the stratosphere whereas the same plays a role as a secondary air pollutant at tropospheric levels. This review encompasses studies involving the science of ozone destruction with an emphasis on chemical processes involved, minimum ozone features, ozone hole area characteristics, various Ozone Depleting Substances (ODSs), consequences of reduced stratospheric ozone levels, and the different executed international commitments to restrain ozone depletion. It has been perceived that the decrease in stratospheric ozone volume gives away extensively to climate change such as through ozone chemistry fluctuations of polar annular modes and its Greenhouse Gas (GHG) features. Different international ozone layer protection agreements have been performing a major role in limiting stratospheric ozone depletion thereby its adverse effects, and specifically Montreal protocol has been a great success to this point. ER